Origin, Genetic Diversity, and Evolutionary Dynamics of Novel Porcine Circovirus 3 - Li, Gairu (Adv Sci (Weinh), 2018)
Porcine circovirus 3 (PCV3) is a novel virus associated with acute PDNS (porcine dermatitis and nephropathy syndrome)‐like clinical signs identified by metagenomic sequencing from swine. Its high occurrence may pose a potential threat to the swine industry worldwide. The processes resulting in the emergence and spread of PCV3 remain poorly understood. Herein, the possible origin, genotypes, and evolutionary dynamics of PCV3 based on available genomic sequences are determined. The closest ancestor of PCV3 is found to be within the clade 1 bat CVs. Using different phylogenetic methods, two major genotypes are identified, PCV3a and PCV3b. It is found that the effective population size of PCV3 increased rapidly during late 2013 to early 2014 and this is associated with the diversification of PCV3a and PCV3b. A relatively high effective reproductive number (Re) value and higher evolutionary rate were found compared to other single‐stranded DNA viruses, and positive selection on codons 122 and 320 (24 of ORF2) is identified. It is hypothesized that this, together with the prediction of a potential change of an antigenic epitope at position 320, might have allowed PCV3 to escape from the host immune response. Overall, this study has important implications for understanding the ongoing PCV3 cases worldwide and will guide future efforts to develop effective preventive and control measures.